Anorexia of ageing: a key component in the pathogenesis of both sarcopenia and cachexia. Issue 4 (27th April 2017) - Morley, John E.
Abstract: The anorexia of aging was first recognized as a physiological syndrome 30 years ago. Its major causes are an alteration in fundal compliance with an increase in antral stretch and enhanced cholecystokinin activity leading to increased satiation.This anorexia leads to weight loss in aging persons and is one of the component causes of the aging related sarcopenia. This physiological anorexia also increases the risk of more severe anorexia when an older person has an increase in inflammatory cytokines such as occurs when they have an illness. This results in an increase in the anorexia due to cachexia in older persons.